Gray matter reduction is associated with cognitive dysfunction in depressed patients comorbid with subclinical hypothyroidism - Zhao, Shuai; Du, Yishan; Zhang, Yu; Wang, Xiaoqin; Xia, Yi; Sun, Hao; Huang, Yinghong; Zou, Haowen; Wang, Xumiao; Chen, Zhilu; Zhou, Hongliang; Yan, Rui; et al. (Frontiers in Aging Neuroscience, 2023)
To explore the association between regional gray matter volume (GMV) and cognitive impairments and ascertain whether the regional brain alterations related to cognitive impairments occur in major depressive disorder (MDD) patients with comorbid subclinical hypothyroidism (SHypo). We enrolled 32 MDD patients, 32 MDD patients with comorbid SHypo, and 32 normal controls and subjected them to thyroid function tests, neurocognitive tests, and magnetic resonance imaging (MRI). Using voxel-based morphometry (VBM) analysis, we examined the pattern of gray matter (GM) in these participants. We also used ANOVA to detect group differences and partial correlation to explore the potential association between GMV alterations and cognitive tests in comorbid patients. The comorbid patients exhibited significantly smaller GMV in the right middle frontal gyrus (MFG) than the non-comorbid group. Furthermore, the partial correlation analysis showed that GMV of the right MFG was associated with poor executive function (EF) performance in the comorbid patients. These findings provide valuable insight into the relationship between the alteration of GMV and cognitive dysfunction of MDD patients with comorbid SHypo.